Shifting Polri's Law Enforcement Strategy: Restorative Justice for Public Trust - Firdaus, Muhammad; Dwilaksana, Chryshnanda; Onielda, Muhammad Daffa Auliarizky (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Restorative justice has gained importance within the Indonesian National Police as a means of law enforcement and security services in the era of globalization and modernization. This approach offers a humane alternative that focuses on the recovery of victims and offenders, aiming to prevent crime and resolve conflicts. The police have transitioned from a purely punitive approach to embracing restorative justice principles. Community policing is crucial for reducing crime rates and fostering public trust. The challenge lies in shifting the law enforcement paradigm towards restorative justice and implementing community policing to build public trust. The research methodology involves normative legal research with an empirical approach, employing a descriptive-analytical nature. Secondary and primary data are used for analysis. Qualitative analysis and deductive conclusions are drawn. Findings indicate that the integration of restorative justice within community policing is an effective solution to improve the relationship between the community and the police. It is recommended that the police introduce the restorative justice approach in their community policing programs, thereby shifting the law enforcement paradigm and fostering public trust. This research emphasizes the significance of restorative justice in the context of community policing and its potential impact on law enforcement practices and public perception of the police